2020
DOI: 10.1002/mnfr.202000232
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Milk Fat Globule Membrane Restores Decreased Intestinal Mucosal Barrier Development and Alterations of Intestinal Flora in Infant‐Formula‐Fed Rat Pups

Abstract: Scope: Milk fat globule membrane (MFGM), which contains abundant polar lipids and glycoproteins, can narrow the gap in growth and development between breast-fed and infant-formula-fed babies. The objective of this study is to evaluate the effect of MFGM supplementation in infant formula on intestinal epithelium maturation, tight junctions, and gut colonization in rat pups. Methods and results: Sprague Dawley rat pups consume one of the five diets from postnatal day 8, including rat breastfeeding (BF), infant f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 51 publications
2
14
0
Order By: Relevance
“…In our previous study, MFGM supplementation increased TJ proteins and alleviated intestinal inflammation in obese mice, thereby enhancing intestinal barrier [24]. MFGM restored the intestinal development through increasing TJ proteins expressions, promoting intestinal proliferation and differentiation in infant formula-fed pups [25]. Based on these studies, MFGM could exert beneficial effects on immunomodulation and intestinal barrier.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In our previous study, MFGM supplementation increased TJ proteins and alleviated intestinal inflammation in obese mice, thereby enhancing intestinal barrier [24]. MFGM restored the intestinal development through increasing TJ proteins expressions, promoting intestinal proliferation and differentiation in infant formula-fed pups [25]. Based on these studies, MFGM could exert beneficial effects on immunomodulation and intestinal barrier.…”
Section: Introductionmentioning
confidence: 81%
“…PCR reactions were conducted as previously described. Briefly, the V3 to V4 regions of the bacterial 16S rRNA gene were amplified in accordance with a previous study [25]. PCR reactions were conducted in 20 µL mixture including 10 ng DNA template, 0.4 μL FastPfu Polymerase, 0.8 μL each primer (5 μmol/L), 2 μL dNTPs (2.5 mmol/L), and 4 µL 5 × FastPfu Bufferd and reaction system was carried out under the following procedure: 95 ℃ for 120 s, at 95 ℃ for 30 s by 27 cycles, 55 ℃ for 30 s and 72 ℃ for 45 s and finally 72 ℃ for 10 min.…”
Section: Microbiota Analysis By 16s Rrna Gene Sequencing 2101 Bacteri...mentioning
confidence: 99%
“…Taking the crypt–villi axis as the baseline, IECs are in a highly differentiated status . IECs secrete mucus, antimicrobial peptides, and other chemicals to prevent harmful luminal molecules from entering the systemic circulation . As one of the molecular regulators secreted by intestinal endocrine cells, 5-HT has the function of responding to microbial customization and maintaining the homeostasis of IECs .…”
Section: Discussionmentioning
confidence: 99%
“…Prior work reported that artificial rearing from 7 days of age caused villus atrophy and deeper crypt in the small intestine of piglets ( Vergauwen et al, 2017 ). In rats, infant formula feeding led to stunted villus and decreased the expression of ZO-1, Claudin-3, and Claudin-4 in the ileum ( Gong et al, 2020 ). Singh et al (2020) found that formula feeding resulted in villus loss, a decrease in ZO-1, and apoptosis of intestinal epithelial cells in rat ileum.…”
Section: Discussionmentioning
confidence: 99%